THE MICROWAVE-SPECTRUM OF THE OPEN-SHELL COMPLEX ARNO2 - Low, R; Whitham, C; Varberg, T; Howard, B (1994)
The 505←404, 404←303, 303←202 and 202←101 rotational transitions of the open-shell van der Waals complex ArNO2 have been observed using a Fourier-transform microwave spectrometer. The complex was produced by supersonic expansion of NO2 gas in argon. The spectrum showed fine, magnetic hyperfine and electric quadrupole structure. The data have been fitted to a semi- rigid Hamiltonian to determine the molecular parameters for the KitA=0 state. We discuss the implications of these derived parameters for the electronic and geometric stucture of the complex. © 1994.